Wildlife gardening for collaborative public–private biodiversity conservation. Issue 3 (3rd July 2017) - Mumaw, Laura; Bekessy, Sarah
ABSTRACT: Complementary public and private conservation action is required to sustain native biodiversity in cities. Residents can contribute by wildlife gardening – removing environmental weeds, cultivating indigenous flora, and improving habitat in their gardens. There is currently little guidance about how best to involve residents in wildlife gardening and align their work with public land management. We explored how a purposively chosen wildlife gardening program in Melbourne, Australia engaged and supported residents to augment local government efforts to conserve indigenous biota. Sixteen semi-structured interviews were conducted with program members to understand the program's impact on their gardening and their connections with their council and community. Unpublished Council survey data were used to position interview findings on wildlife gardening activities and the value of program features. Interviewees detailed how they modified their gardening to assist their council to conserve indigenous biota. Five program features were implicated in this change: (1) on-site garden assessment; (2) indigenous community nursery; (3) communication hubs; (4) a framework that fosters experiential learning and community linkages; and (5) endorsement of each garden's potential conservation contribution. Collaborative wildlife gardening programs can engage residents to manage their land to achieve landscape-focused conservation goals while building relationships with council and community.